ЛАТЕНТНІСТЬ ЗЛОЧИНІВ У СФЕРІ СЛУЖБОВОЇ ДІЯЛЬНОСТІ, ЩО ВЧИНЯЮТЬ ПРАЦІВНИКИ НАЦІОНАЛЬНОЇ ПОЛІЦІЇ УКРАЇНИ - Бардачов, Віктор Володимирович (SUPREMANCE OF LAW, 2019)
The article deals with criminological analysis of crimes in the sphere of official activity committed by employees of the National Police of Ukraine. It is established that the specificity of the abuse is determined by the lack of clear regulation of the powers of the employees and their managers, the high level of latency, the combination with related and related crimes. The main causes and conditions contributing to the latency of such crimes are highlighted. The proposed criminological analysis of crime is based only on offi cial statistics, while at the same time a significant number of crimes committed by law enforcement officials (National Police) remain outside the official statistics or even undetected.